Consensus Methods in Multiagent Decision Support System in Small and Medium Enterprises - Sobieska-Karpińska, Jadwiga; Hernes, Marcin (Metody concensusu w wieloagentowym systemie wspomagania decyzji w małych i średnich przedsiębiorstwach, 2009)
The methods of setting consensus in a multiagent decision support systems in small and middle enterprises are presented in this article. the article presents the problem of supporting the decision taking and characterizes multiagent system of decision support. In the next part it shows methods of setting a consensus that is the definition of distance function which is an element of setting a consensus, a definition and characteristic of consensus function and then the postulates of consensus function.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 55, s. 352-362
Keywords: consensus methods; conflict of knowledge; multiagent systems; decision support systems (dss); small and medium enterprises